Temporal Changes in Spatial Patterns of Soil Properties During a Period of Rice Growth - Yagus Wijayanto; Rizqi Aprilia Putri Anggreini; Ika Purnamasari; Suci Ristiyana (JOURNAL OF TROPICAL SOILS, 2023)
Growing rice is complicated because of the interrelationship among production components, one of which is soil conditions. Determination of soil conditions is usually conducted by employing some soil properties. It is no doubt that soil properties have spatial and temporal characteristics. This research used two soil properties: Electrical conductivity (EC) and pH. This study aimed to use and evaluate Inverse Distance Weighted to uncover the temporal changes in pH and EC during the rice growth period. The methods used in the research were field survey, soil sampling, laboratory analysis, and data processing in Geographical Information Systems (GIS). The sample used was 30 and repeated three times under the growth period (vegetative, generative, and ripening). The results showed that there were changes in pH values of the soil in one growing season, and EC values tend to increase from the vegetative to the ripening period.